Inadequate Dietary Diversity among Female Students in Southeast Sulawesi, Indonesia: Influences of Parental Education and Food Budget - Effendy, Devi Savitri; Muchtar, Febriana; Bahar, Hartati; Nurmaladewi, Nurmaladewi; Nirmala, Fifi; Nurjanna, Yustina (Public Health of Indonesia, 2024)
Introduction:Young people in Indonesia persistently grapple with nutritional challenges. Regrettably, there has been insufficient research addressing their distinct nutritional requirements. Objective:This study aims to describe the dietary diversity of female students in Southeast Sulawesi and investigate the associated factors. Methods:A cross-sectional study was conducted among female students in the Public Health Faculty of Halu Oleo University. Using random sampling, 280 participants were selected from five different departments within the faculty. Minimum dietary diversity for women (MDD-W) was assessed using a single 24-hour recall. A cut-off value of 5 was used to determine whether the recommendation was met. Multiple logistic regression was performed to examine the association between independent variables and MDD-W. Results:The mean (±SD) dietary diversity score of the participants was 3.6±1.1, with only 33.3% meeting the minimum recommendation for dietary diversity. In the multivariate analysis, higher maternal education (AOR: 4.4; 95% CI: 2.0, 9.6), higher paternal education (AOR: 3.2; 95% CI: 1.2, 8.2), and monthly food budget (AOR: 1.9; 95% CI: 1.0, 3.7) were significantly associated with achieving adequate dietary diversity.